Art in America (titel varieert : Art in America and Elsewhere (1922-1939)). (New York City, 1913)
Art in America is an illustrated monthly, international magazine concentrating on the contemporary art world in the United States, including profiles of artists and genres, updates about art movements, show reviews and event schedules. It is designed for collectors, artists, art dealers, art professionals and other readers interested in the art world. Founded in 1913,[1] Art in America covers the visual art world, both in the United States and abroad, with a concentration on New York City and contemporary art fairs. Between 1921 and 1939 the magazine was published under the title Art in America and Elsewhere. (wikipedia)
Https://www.artnews.com/c/art-in-america
Online: https://catalog.hathitrust.org/Record/100333519
Engels
Tijdschriften